Pop Culture and New Media Impact of Internet Use in Parenting on Early Childhood Development: Impact of Internet Use in Parenting on Early Childhood Development - Nur Hamzah; Bayu Suratman (Institut Agama Islam Negeri Madura, 2023)
This paper discusses the use of the internet in parenting for early childhood development. This research departs from the phenomenon of many parents giving gadgets and the internet so that children do not interfere with the activities that are being carried out by parents. Therefore, gadgets are a solution to make it easier for parents to do activities, especially gadgets providing online and offline games. Not only that, there is a lot of video content available online that parents consider in parenting. Parents should be active in devising strategies to protect children in the use of the internet and gadgets. One of the steps that parents can take is to find references to the right use of the internet for early childhood. This research is a qualitative research with a descriptive approach. The data collection technique in this study is that the authors collect data through interviews with parents who use the internet in parenting. In addition, the research data of this article is strengthened by research data carried out by other research through literature reviews such as journals, proceedings, books, and online media. This study was conducted to identify the phenomenon of internet use among parents in parenting. The goal is to explore the use of the internet and its impact on early childhood development